Data from: Skeletal adaptations and phylogeny of the oldest mole Eotalpa (Talpidae, Lipotyphla, Mammalia) from the UK Eocene: the beginning of fossoriality in moles - Hooker, Jerry J. (Dryad, 2016)
The oldest talpid, Eotalpa, was previously known only from isolated cheek
teeth from the European late Middle Eocene to earliest Oligocene.
Screenwashing of Late Eocene sediments of the Hampshire Basin, UK, has
yielded cranial and postcranial elements: maxilla, dentary, ulna,
metacarpals, distal tibia, astragalus, calcaneum, metatarsals and
phalanges. In addition to M1–2 myotodonty, typical talpid features are as
follows: ulna with long medially curved olecranon and deep abductor fossa
and astragalar body with lateral process. However, Eotalpa retains certain
soricid-like primitive states (M1 preparacrista, P4 with prominent
mesiolingual protocone lobe, strongly angled astragalar neck and calcaneum
with no space for a cuboid medial process) not found in modern talpids.
Eotalpa is more derived than the most primitive living talpid Uropsilus in
having lost the M1–2 talon shelf, developed a convex radial facet on the
ulna, an incipient proximal olecranon crest, relatively shorter
metapodials and depressed manual unguals. Its astragalus with medial
trochlear ridge taller than the lateral one and massive medial plantar
process is typical of the Lipotyphla. Eotalpa lacks synostosis of tibia
and fibula, found in other Talpidae, Soricidae and Erinaceidae, suggesting
that synostosis in these groups has been independently acquired. Cladistic
analysis places Eotalpa as stem member of the Talpidae and shows that much
homoplasy arose during the early evolution of the family. Ground dwelling
in Eotalpa is indicated by the following: astragalus with a medially
dipping head, curved in a single plane; calcaneum with distal peroneal
process and strongly overlapping ectal and sustentacular facets; and
matching sized ectal and sustentacular facets on calcaneum and astragalus.
These features would have restricted ankle mobility. Ungual and metatarsal
shape and ulnar structure suggest a primitive stage in fossorial evolution
and argue against a semiaquatic precursor stage in talpid fossoriality.
Shrew-moles may represent a reversal to surface foraging rather than an
intermediate stage in fossoriality.
SupportingInformationAppendix S1. Description of numbered characters used
in the cladistic analysis. Appendix S2. Character-taxon matrix used in the
cladistic analysis. Appendix S3. Character states at numbered nodes in the
cladogram.
Keywords: Talpidae; Cladistic analysis; Lipotyphla; Paleocene-Oligocene; Eocene; Fossoriality; Eotalpa